Pendidikan Akhlak Terhadap Pembentukan Karakter Siswa di Era Digital - Yuli Setyawati; Nisrina; Kamila Nayli Az-Zahra; Fathiyah Husna; Nuril Azzam Saeful Fikri; Syaefudin Achmad (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2026)
The development of digital technology has brought significant changes in students' mindsets, attitudes, and behaviors, which have a direct impact on the formation of their character and morals. The digital era presents moral challenges in the form of a rapid flow of information, virtual social interactions, and easy access to content that does not always align with ethical and religious values. This study aims to analyze the role of moral education in shaping students' character in the digital era. This study used a descriptive qualitative approach with library research methods, through a review of books, scientific journals, and previous research relevant to moral education, character education, and the dynamics of the digital era. Data analysis techniques used content analysis and qualitative descriptive analysis to gain a comprehensive understanding. The results of the study indicate that moral education plays a strategic role in shaping students' character, particularly in instilling the values ​​of honesty, responsibility, empathy, courtesy, and moral integrity. However, moral education depends heavily on the ability of educators, educational institutions, and families to integrate moral values ​​with digital literacy in a contextual and adaptive manner. Therefore, moral education remains a key pillar in shaping student character in the digital age when implemented through a holistic, collaborative, and contemporary approach.